Effect of regional citrate anticoagulation on thrombogenicity and biocompatibility during CVVHDF - Polanská, Kamila; Opatrný, Karel; Rokyta, Richard; Krouzecký, Ales; Vit, Ladislav; Kasal, Eduard (Renal failure, 2006)
This study was designed to assess the principal markers of thrombogenicity and biocompatibility during continuous veno-venous hemodiafiltration (CVVHDF) using regional citrate anticoagulation (RCA). In a prospective study, 11 procedures with a polysulfone membrane were performed in nine critically ill patients with acute renal failure and impaired hemostasis. Blood samples were taken before and during CVVHDF at diafilter outlet--before calcium-induced reversal of the effect of citrate--at 15, 60, 360, and 1440 minutes. In four patients, 10 CVVHDF sessions were performed with systemic heparin anticoagulation (HA) using a polyacrylonitrile membrane. During RCA, blood thrombocyte count, plasma thrombin-antithrombin III complexes, beta-thromboglobulin, and von Willebrand factor levels did not differ significantly from baseline. Plasma D dimer levels rose significantly at 360 minutes; however, the difference between diafilter inlet and outlet levels was nonsignificant. There was a significant increase in plasma C5a concentrations and a decline in blood leukocyte count in the early phase of CVVHDF. Just as in RCA, no increase in plasma thrombogenicity indices was observed during HA. However, clotting times in blood entering patients' circulation were significantly prolonged. Plasma C5a concentrations increased significantly at the beginning of CVVHDF. RCA can effectively inhibit the thrombogenic effect of the extracorporeal circuit in CVVHDF. The effect of HA may be similar, however, at the expense of systemic anticoagulation and risk of bleeding. RCA, performed in a way that overcomes thrombogenicity, does not completely eliminate complement activation and/or transient leukopenia during CVVHDF.
Keywords: heparin; Heparin; Acute Kidney Injury; Anticoagulants; Citrates; Sodium Citrate; lidé; Aged; citronan sodný; trombóza; senioři; hemodiafiltrace; Thrombosis; Hemodiafiltration; Humans; citráty; akutní poškození ledvin; antikoagulancia